Past and current trends in defining and measuring poverty in the EU - Gülðsah Sedefoæglu (Technische Hochschule Rosenheim, 2023)
In this research, we discuss the past and current trends in defining poverty to look at the topic from different perspectives and to provide an outline of future work that we aim to complete the picture on the qualitative and quantitative side. For this purpose, our focus here is to evaluate the diversity of definitions and to emphasize how important it is to combine subjective and objective approaches for practical policy analysis. As a first step of our future work, we also present the pilot study results to assess the results comparatively in the EU states and Türkiye.
urn:nbn:de:bvb:861-opus4-23011
Keywords: 330; European Union; Türkiye; poverty